2013
DOI: 10.1037/spq0000027
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of feedback and repeated readings on oral reading fluency: Let’s not forget prosody.

Abstract: Although extensive research supports repeated readings (RR) as an intervention for improving reading fluency, it largely ignores reading prosody, which is a key component of reading fluency. The current study extends the RR literature by examining the impact of RR on prosody and whether the content of directions and feedback might impact what components of fluency are improved. Elementary students (N = 76) were randomly assigned to either a rate- or prosody-focused RR intervention. The study differs from exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
4
24
0
2
Order By: Relevance
“…Na verdade, a entonação, a leitura enfática e o fraseamento, têm sido associadas tanto à fluência (Ardoin, Morena, Binder, e Foster, 2013;Schrauben, 2010) como à compreensão da leitura (Arcand et al, 2014;.…”
Section: Prosódia Na Linguagem E Na Leituraunclassified
“…Na verdade, a entonação, a leitura enfática e o fraseamento, têm sido associadas tanto à fluência (Ardoin, Morena, Binder, e Foster, 2013;Schrauben, 2010) como à compreensão da leitura (Arcand et al, 2014;.…”
Section: Prosódia Na Linguagem E Na Leituraunclassified
“…According to the theory of automatic word processing (LaBerge & Samuels, 1974;Logan, 1988), word recognition automaticity is indispensable for reading fluency, which in turn is a key foundation for text comprehension (Miller & Schwanenflugel, 2006;Paige, 2011). If individuals must invest too much of their cognitive resources in executing their phonological skills and consequently demonstrate slowed oral language processing speed, their opportunities to focus on meaning are highly limited (Ardoin, Morena, Binder, & Foster, 2013;Swain, Leader-Janssen, & Conley, 2013). Thus, to be able to extract meaning from print, one must first acquire the skill of decoding words quickly, accurately, and effortlessly (Lee & Yoon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from applied research on RR demonstrate that repeated practice can improve reading for numerous populations, including skilled readers (Ardoin, Morena, Binder, & Foster, 2013 ;Levy, Nicholls, & Kohen, 1993 ;Sindelar, Monda, & O ' Shea, 1990 ), readers with learning disabilities (Chard et al, 2002 ), and all students through fourth grade (NICHD, 2000 ). In a meta-analysis of RR research, Therrien ( 2004 ) analyzed mean improvements on reread passages, and reported effect sizes of .83 for fluency and .67 for comprehension.…”
Section: Introductionmentioning
confidence: 99%